SHARIA ECONOMIC LAW PERSPECTIVE ON ONLINE MEETING PREMIUM ACCOUNT LEASING - Nurjaman, Muhamad Izazi; Hakim, Sofian Al-; Setiawan, Iwan; Witro, Doli; Sahid, Mualimin Mochammad (Journal of Islamic Economic Laws, 2022)
In general, in leasing, the object of the contract is the benefit of a tangible object. However, it is different from renting a Zoom Meeting Premium account whose position is as application software. So that its position will have benefits if its use has collaborated with hardware as hardware. Meanwhile, what is being rented is the software only. Therefore, this study will discuss the rental of Zoom Meeting Premium accounts according to the perspective of sharia economic law. This research uses a descriptive case study method with an empirical juridical approach. The data analysis technique was carried out through three stages namely data reduction, data presentation and conclusions. This study found that the position of Zoom Meeting is premium as a software application that is part of a computer program. At the same time, the computer program is part of the copyright in the form of intangible movable objects. So that there is the development of the object of the ijarah contract, generally in the form of benefits from tangible objects, which can also be in the form of benefits from intangible objects. However, the development of intangible objects as contract objects needs to be studied further by researchers so that they can be applied to all contract objects, such as intangible objects becoming objects of buying and selling contracts, mudharabah, musyarakah and other contracts.